2015
DOI: 10.1016/j.cj.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 42-year long-term fertilizer management on soil phosphorus availability, fractionation, adsorption–desorption isotherm and plant uptake in flooded tropical rice

Abstract: Soil phosphorus (P) fractionation, adsorption, and desorption isotherm, and rice yield and P uptake were investigated in flooded tropical rice (Oryza sativa L.) following 42-year fertilizer and manure application. The treatments included low-input [unfertilized control without N, P, or K (C 0 N 0 )], farmyard manure (FYM) (C 1 N 0 ), NP (C 0 NP), NPK (C 0 NPK), FYM + NP (C 1 NP), and high-input treatment, FYM + NPK (C 1 NPK). Grain yield was increased significantly by 74% over the control under the combined ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The results of leaching and distribution of P in the columns show that there was a translocation of P from layers with lower binding energy to layers with higher binding energy, with the soil acting as a sink. Studies have shown that long-term fertilization with manure can promote changes in P adsorption influencing its dislocation into deeper layers of the soil profile (del Campillo et al 1999;Silva and Menezes 2007;Galvão et al 2008;Xavier et al 2009;Tarkalson and Leytem 2009;Ojekami et al 2011;Abdala et al 2012;Bhattacharyya et al 2015). In this regard, leaching of P may occur in soils saturated with P, even if there is no excessive input of P. Nelson et al (2005) found higher values of leached P than P in the inputs for soils saturated with P when precipitation was above the average, indicating that desorption of P contributed to 50% of leached P.…”
Section: Adsorption and Desorption Of Pmentioning
confidence: 99%
“…The results of leaching and distribution of P in the columns show that there was a translocation of P from layers with lower binding energy to layers with higher binding energy, with the soil acting as a sink. Studies have shown that long-term fertilization with manure can promote changes in P adsorption influencing its dislocation into deeper layers of the soil profile (del Campillo et al 1999;Silva and Menezes 2007;Galvão et al 2008;Xavier et al 2009;Tarkalson and Leytem 2009;Ojekami et al 2011;Abdala et al 2012;Bhattacharyya et al 2015). In this regard, leaching of P may occur in soils saturated with P, even if there is no excessive input of P. Nelson et al (2005) found higher values of leached P than P in the inputs for soils saturated with P when precipitation was above the average, indicating that desorption of P contributed to 50% of leached P.…”
Section: Adsorption and Desorption Of Pmentioning
confidence: 99%
“…Previous literatures have reported that insoluble IP can be dissolved by low molecular weight organic acids (e.g., citric and gluconic acids) produced and released by both phosphorus solubilizing bacteria (PSB) and fungi (Sashidhar and Podile, 2009;Ogbo, 2010;Patel et al, 2011), and OP can be digested by extracellular enzymes (e.g., phosphatase and phytase) mainly synthesized and secreted by microbes (Tan et al, 2016;Neal et al, 2017). Previous literatures have reported that repeated utilization of fertilizers exacerbates soil quality and lessens phosphorus availability (Bhattacharyya et al, 2015;Liu et al, 2018). To achieve the aim of sustainable agriculture, the application of phosphorus solubilizing microbes with multiple P sources utilizing abilities provides a new approach to improve soil quality.…”
Section: Introductionmentioning
confidence: 99%
“…The limited availability of phosphorus (P) for rice plant growth in highly weathered acid soils of tropics and sub-tropics is an emerging threat to the food security of the half of the world's population (FAO-STAT, 2016). Rice production is mainly constrained by low P-use efficiency (PUE) and P-recovery efficiency (PRE) in acid soils (Fageria et al, 2015), because P added to acid soils is fixed (50 to 90 % of applied phosphatic fertilizer) as insoluble phosphates of Al +3 and Fe +2 (Bhattacharyya et al, 2015;Redel et al, 2016). Though the application of phosphatic fertilizers had dramatically increased yields of rice from an acreage of 30-40% of world's arable land (Bijay-Singh and Singh, 2017) those belong to Inceptisols, Oxisols, Alfisols, and Ultisols concentrated in Brazil, Columbia, Venezuela, Central Africa, and Southeast Asia, but low PUE (< 20 to 25%) and PRE (approximate 10%) has been reported (von Uexküll and Mutert, 1995;Wardle et al, 2004;Fageria et al, 2014).…”
Section: Introductionmentioning
confidence: 99%